Improving the Potency of N-Aryl-2,5-dimethylpyrroles against Multidrug-Resistant and Intracellular Mycobacteria - Touitou, Meir; Manetti, Fabrizio; Ribeiro, Camila Maringolo [UNESP]; Pavan, Fernando Rogerio [UNESP]; Scalacci, Nicolò; Zrebna, Katarina; Begum, Neelu; Semenya, Dorothy; Gupta, Antima; Bhakta, Sanjib; Mchugh, Timothy D.; Senderowitz, Hanoch; et al. (American Chemical Society (ACS), 2020)
A series of N-phenyl-2,5-dimethylpyrrole derivatives, designed as hybrids of the antitubercular agents BM212 and SQ109, have been synthesized and evaluated against susceptible and drug-resistant mycobacteria strains. Compound 5d, bearing a cyclohexylmethylene side chain, showed high potency against M. tuberculosis including MDR-TB strains at submicromolar concentrations. The new compound shows bacteriostatic activity and low toxicity and proved to be effective against intracellular mycobacteria too, showing an activity profile similar to isoniazid.
Keywords: antimycobacterial drug; drug resistance; intracellular tuberculosis; pyrroles; Tuberculosis